A midsummer night's fudge - Coco, Nancy (Coco, Nancy. Candy-coated mystery., 2022)
"During the Midsummer Night's Festival, Allie decides to take her bichonpoo, Mal, home to spare her furry little ears from the sounds of fireworks. But on her way back, Allie spots a body in the lake. Just minutes ago, Winona Higer was crowning the event's Queen--could the competition have really been that deadly? While she ponders the mystery the next morning, Allie prepares her favorite dark chocolate cherry fudge recipe. But she's soon recruited to sub for the late Winona and serve as parade float judge, among other duties. As she hears rumors and gossip, and learns of mean pranks and threatening notes, her instincts kick in--despite her boyfriend the cop's disapproval. Now, between managing a new hire and keeping the tourists filled with fudge, she's dealing with a case that's boiling over." --Provided by Publisher.